Prevalência de demência em pacientes com doença de Parkinson - SALOMÃO, Brena Giselli Cei (2023)
Idiopathic Parkinson’s disease (PD) is characterized by reduced nigrostriatal and cortical dopaminergic influence, with changes in movement and, subsequently, behavioral and cognitive disturbances, including dementia, which has its prevalence increased with age, being essentially a disease of the aged. The purpose of this research is to study the prevalence of dementia in individuals of DP, assessing the cognitive impairment of 30 patients. All patients underwent the following assessments: cognitive function by the Mini-Mental State Examination (MMSE); memory by List of Words for fixing and Recall (LWFR); commitment of attention in the test of Verbal Fluency (animals) and executive functions and visuoespaciais as the clock drawing test. A descriptive study was conducted by the application of the research protocol and tests previously cited. The patients were mostly male (63.3%), in the age group of 60-65 years old (43.3%), presenting between 1-7 years of schooling (56.7%). For testing, the MMSE showed to be amended in 20% of cases, the LWFR in 66.7%, the Verbal Fluency in 26.6% and 40% clock drawing with serious commitment. As the MMSE the main method of screening, concluded that the prevalence of dementia in the study population was 20%.